Application of ultrasonic testing & V(z) technique to study stress - Wong, Raymond Xu Wen. (2011)
Non-Destructive Testing (NDT) is widely used in the industrial field especially in aerospace industries where the integrity of the components is ensured to be free of defects. Defects can be formed from a lot factors. Stress is one of the factors.